THE RESULTS OF THE DIAGNOSTICS OF THE TECHNICAL CONDITION OF THE OPERATED METAL DRAWBRIDGE TEST UNDER THE COMBINED DRIVE - Tarasenko, V. P.; Savchynskyi, B. V.; Solomka, V. I.; Sukhorukov, B. D.; Zhurbenko, M. K.; Kharytonova, T. F.; Kliuchnyk, S. V. (Science and Transport Progress, 2007)
The article describes peculiarities of operation of the draw-bridge for combined traffic, the results of technical evaluation and tightness tests of the suspended cables of the drawbridge with vertically lifted span structure.